Prevalence and antimicrobial susceptibility profiles of Staphylococcus aureus nasal carriage among pre-clinical and clinical medical students in a Tanzanian University. (December 2016) - Okamo, Benard; Moremi, Nyambura; Seni, Jeremiah; Mirambo, Mariam; Kidenya, Benson; Mshana, Stephen
Abstract Background Methicillin resistantStaphylococcus aureus (MRSA) nasal carriage is a potential niche for spread and a risk factor for subsequent infections. Despite the fact that medical students are exposed to patients in the hospital during their training, information onS. aureus and MRSA nasal carriage among medical students in Tanzania remains to be dearth so as to guide appropriate infection control and preventive measures. Methods A cross-sectional study involving 314 medical students, pre-clinical (n = 166) and clinical (n = 148), at Catholic University of Health and Allied Sciences (CUHAS) was conducted from February to June 2013. Nasal swabs from eligible students were taken and processed using standard operating procedures so as to identifyS. aureus, MRSA and their respective antimicrobial susceptibility patterns. Results The median age (interquartile range) of the study participants was 24 (22–27) years with approximately 69.4 % being males.S. aureus accounted for 21.0 % (66/314) of which 1.5 % (1/66) was MRSA; giving an overall MRSA nasal carriage prevalence of 0.3 % (1/314).Staphylococcus aureus carriage among pre-clinical and clinical students were 19.9 % (33/166) and 22.3 % (33/148) respectively. MRSA carriage was found in one preclinical student with history of working in hospital for years prior to join CUHAS.Staphylococcus aureus carriage was significantly more in older median age group among clinical students compared to preclinical students (p < 0.001). Majority of the isolates were resistant to Ampicillin (87.9 %, 58/66) while all were sensitive to Ciprofloxacin and Vancomycin. Conclusion There is high prevalence ofS. aureus carriage among medical students at CUHAS. Fortunately, MRSA was found in only one student. In the light of these findings, focused MRSA surveillance to other potential sources like health care workers, patients and environment should be carried out in this setting.